Specifics of Developing Professional Thinking in Law Students - Sergeeva, Marina Georgiyevna (2021)
The article examines the essence, role and significance of professional thinking within lawyers’ professional development, making a special emphasis on the specifics of evolving law students’ professional thinking. The research purpose is a theoretical and empirical study of the developmental specifics of law students’ professional thinking. Besides, there is a focus on the structure and features of lawyers’ professional thinking as a special professionally important quality. The authors conduct a comprehensive analysis of the developmental specifics of law students’ professional thinking, propose their own definition of this concept and consider its structure and structural components. The analysis of relevant literature contributed to studying the validity of the chosen topic. The article also reflects the methodology of research and its algorithm that include conducting a complex psychological and pedagogical experiment, assessing the declared parameters and fulfilling the statistical analysis of the results based on methods such as variance analysis, correlation analysis using Marsch’s I coefficient, Friedman’s R coefficient and Kruskal – Wallis H-criterion. The research base was the International Law Institute (Moscow, Russia). The experimental and control groups of subjects were formed, numbering 60 people representative in gender, etc. The results of the study demonstrate the effectiveness of combining trainings, special courses and the evolvement of formal-logical reasoning within the development of law students’ professional thinking.